Improvement in Performance and Emission Using Coconut Oil as a Diesel Substitute - Pandey, Rajesh Kumar; Rehman, A; Sarviya, R M; Dixit, Savita (Hydro Nepal: Journal of Water, Energy and Environment, 2010)
Diesel engines, unlike their petrol counterparts, are omnivorous in fuel consumption habits and can easily run on vegetable oils without any major changes in the engine. Using raw oils in diesel engines led to such problems as the sticking of fuel injectors and piston rings due to choking, and the thickening of lubricating oils, resulting in clogging of filters, but these were overcome in a large measure by pre-conditioning of the fuel by a chemical process using methanol or ethanol called ‘Transesterification'. Coconut oil can be adapted as additive fuel for the existing bio diesel engines without major modifications. If diesel engines turn vegetarian in our country, which has a great potential for producing vegetable oils from the evergreen tropical forests and plantations, it will be a big achievement in terms of reducing the sky-rocketing petroleum bills! Edible coconut oil is subjected to Transesterification process to reduce its viscosity and resulting coconut methyl ester known as biodiesel used in 5 H.P. Single cylinder diesel engines. Result shows that heated B-100 blend gave better performance and produced lower smoke emission than other fuel blends. Key words: C.I. engine; Diesel; Biodiesel; Coconut oil; Engine emissions DOI: 10.3126/hn.v5i0.2494 Hydro Nepal Vol. 5, July 2009 Page:62-65